Workshop Teknik Kelompok sebagai Strategi Efektif Meningkatkan Kompetensi Guru dalam Penyusunan Instrumen Penilaian - Basuki Jaka Purnama (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2022)
The competence of teachers in constructing instruments of assessment greatly affects the accuracy of measuring the achievement of students’ competence. This study aims to: (1) improve the competence of teachers in preparing assessment instruments and (2) obtain the information of the workshop implementation on improving the teachers of SMA Negeri 1 Kalasan competence in developing assessment instruments. This research is an action research which was conducted in semester 1 of the 2020/2021 academic year for 4 months with 10 teachers as the research subjects. This action research used the Kemmis and Taggart models with two cycles, each cycle consisted of two meetings with the stages of planning, action, observation, and reflection. The data collection was done through observation and product assessment. The data analysis was carried out by scoring and calculating the final score of the observed and assessed activities. The results of the study indicate that the workshop can improve the competence of the teachers in constructing assessment instruments in the form of a grid of questions and items. This was proven by an increase in the ability to compose a grid of questions from 75.88% (poor) in the first cycle to 88.25% (able) in the second cycle and an increase in the ability to construct the items from 77.42% (poor) in the first cycle to 88.89% (able) in the second cycle. It means that the teacher's competence has met the indicator of a successful action at 80%. Based on these results, it can be concluded that the workshop has really improved the competence of the teachers of SMA Negeri 1 Kalasan in constructing the grids and test items.